Analyzing the Performance of Reverse Osmosis Membranes After the Cleaning Process: Case study Performed at PT. XYZ. - Afandy, Moh. Azhar; Khatimah, Khusnul; Sawali, Fikrah Dian Indrawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
PT. XYZ uses a reverse osmosis (RO) system in demin water treatment. One of the weaknesses of the RO system is the formation of fouling on the membrane, which can reduce the performance of the membrane, so it is necessary to carry out an appropriate cleaning process to remove deposits on the surface of the membrane, restore the separation characteristics, and restore the normal capacity of the system. This research aims to examine the effect of cleaning on the performance of reverse osmosis membranes in the PT. XYZ with requirements for reverse osmosis membrane type FILMTEC BW30–400 IG. The research was conducted for 8 weeks by collecting data on the reverse osmosis control box and control room in the form of product flow rate, feed conductivity, and product conductivity. Based on the results of the study, it can be concluded that the effect of cleaning on membrane performance can only extend the life of the membrane and cannot meet the specifications for the working parameters of the reverse osmosis membrane, which can be seen in the salt rejection, salt passage, and flux values obtained in this study.